Pseudobulbar affect: Prevalence and association with symptoms in multiple sclerosis. Issue 6 (December 2018) - Fitzgerald, Kathryn C.; Salter, Amber; Tyry, Tuula; Fox, Robert J.; Cutter, Gary; Marrie, Ruth Ann
Abstract : Background: We sought to determine the prevalence of pseudobulbar affect (PBA) in a large MS population and assess its association with disability and symptom severity. Methods: North American Research Committee on MS (NARCOMS) registry participants completed the Center for Neurologic Study-Lability Scale (CNS-LS), a validated 7-question self-report measure of PBA. A composite PBA score was derived from the sum of responses to the 7 questions. We categorized individuals as PBA-positive (PBA[+]) if they had a composite score ≥17 without current depression. Participants also reported their demographic characteristics and their clinical characteristics using Patient-Determined Disease Steps and Performance Scales. We compared clinical and disease characteristics for PBA(+) responders with those without PBA using descriptive statistics and multivariable multinomial logistic regression. Results: Of the 8, 136 responders, 574 (7%) had scores ≥17 on the CNS-LS; however, only 200 (2.5%) individuals had scores ≥17 without comorbid depression, of whom only 22 (11%) reported a diagnosis of PBA. PBA(+) individuals tended to be younger (mean [SD] 53.4 [11.0] vs 57.2 [10.3] years), non-white (13% vs 9%), and have lower socioeconomic status (⩽30, 000 annual income: 28% vs 22%). In multivariable models, PBA(+) was associated with increased odds of more severe cognitive impairment (moderate vs mild disability OR: 1.37; 95% CI: 1.01, 1.84). Conclusions: Our findings suggest that the prevalence of PBA in MS is low, but similar symptoms may co-occur or overlap with depression, highlighting the importance of concomitant assessment of mood when evaluating potential PBA. PBA may be associated with cognitive impairment in people with MS.